2016
DOI: 10.1152/jn.00775.2015
|View full text |Cite
|
Sign up to set email alerts
|

CaV3.2 T-type Ca2+channels mediate the augmented calcium influx in carotid body glomus cells by chronic intermittent hypoxia

Abstract: ] i ) in glomus cells, the primary oxygensensing cells, is an essential step for carotid body activation by hypoxia. In the present study, we examined the effects of CIH on the glomus cell [Ca 2ϩ ] i response to hypoxia and assessed the underlying mechanisms. Glomus cells were harvested from adult rats or wild-type mice treated with 10 days of either room air (control) or CIH (alternating cycles of 15 s of hypoxia and 5 min of room air; 9 episodes/h; 8 h/day). CIH-treated glomus cells exhibited an enhanced [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 38 publications
(31 reference statements)
0
12
0
Order By: Relevance
“…However, PEG‐catalase had no effect on induction of sensory LTF in the present study and, as such, our data do not support a role for H 2 O 2 , proposed as the mechanistic lynch pin between O 2·¯ and glomus cell Cav3.2 modification in CIH‐preconditioned sensory LTF (Makarenko et al . ).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…However, PEG‐catalase had no effect on induction of sensory LTF in the present study and, as such, our data do not support a role for H 2 O 2 , proposed as the mechanistic lynch pin between O 2·¯ and glomus cell Cav3.2 modification in CIH‐preconditioned sensory LTF (Makarenko et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…) and a T‐type voltage‐gated calcium channel, type 3.2 (CaV3.2) (Makarenko et al . ). However, sensory LTF induced by acute stimuli in the absence of CIH preconditioning may be mediated by a different mechanism.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…), and it has recently been suggested that the Cav3.2 channel subtype mediates the CB over‐activation induced by chronic intermittent hypoxia (Makarenko et al . ). On the other hand, Cav3.2 mRNA is up‐regulated by chronic hypoxia in an Hif2α‐dependent manner in PC12 and chromaffin cells (del Toro et al .…”
Section: Discussionmentioning
confidence: 97%
“…IH increases ROS levels in glomus cells, the primary O 2 sensing cells of the CB (Makarenko et al . ), nucleus tractus solitarious and rostral ventrolateral medulla, the two major brainstem areas associated with processing of sensory information from the CB, and, in AM, a major end organ of the sympathetic nervous system (Kumar et al . ; Souvannakitti et al .…”
Section: Discussionmentioning
confidence: 99%